Synthesis and Characterization of Copper(II) Complexes of New Potentially Binuclear Schiff Base Ligands - MOHAMMADI, HAMIDKHAN (Asian Journal of Chemistry, 2010)
Three new decadentate potentially binucleating Schiff base ligands have been synthesized by condensation of 3,5-di-tert-butyl salicylaldehyde with branched EDTA like hexamines, which, in terms of their structure, corresponded to dimethylene, tetramethylene and hexamethylene-linked 1,5-diamino-3-aza-pentane units. These ligands have two sets of quinquedentate coordination sites separated by polymethylene diamines. The ligands have been characterized by IR, 1H and 13C NMR, UV-Vis and elemental analysis data. The binuclear Cu(II) complexes of these ligands have been prepared and their spectral properties have been studied.